Maintaining the Magic: Adapting Practice Pedagogies Across Course Modalities. Issue 1 (1st January 2023) - Kepple, Nancy; Coles, D. Crystal
ABSTRACT: Social work programs are facing the need to gain further clarity about how to leverage instructional strategies specific to the course modality (i.e., traditional, hybrid, online hybrid, and fully online). At its heart, this challenge is an analogical transfer problem: practice instructors must adapt what they do in one modality to new modalities through modifying how they guide students to master learning objectives. In doing so, instructors can maintain the essence of what makes a practice course work. The discussion is subsequently shaped around common modalities that programs offer (1) traditional courses; (2) hybrid courses (in-person/online); (3) online hybrid courses (synchronous/asynchronous online); and (4) fully asynchronous online courses. This paper presents an organizing framework that explains pedagogical choices by structures (i.e., space, time, and people) and processes (i.e., interactivity). It then provides examples of how practice instructors can navigate the unique strengths and limitations that simultaneously facilitate and constrain interactions between students and instructors, their peers, and the instructional content. As instructors grapple with the inevitable shifts within the academy, they require specific tools to help them generalize existing skills. The proposed framework is an important first step to help shape and evaluate best practices across and within modalities.